2009
DOI: 10.1007/s00296-008-0774-6
|View full text |Cite
|
Sign up to set email alerts
|

Wegener’s granulomatosis complicated by central diabetes insipidus and peripheral neutrophy with normal pituitary in a patient

Abstract: Wegener's granulomatosis (WG) is a necrotizing systemic vasculitis that any organ system can be involved in. We report a patient who was hospitalized with recurrent nodules in pulmonary computed tomograph and symptoms such as intermitted fever, polydipsia, insensibility and pain on extremities. Laboratory investigation showed positive antineutrophil cytoplasmic antibody in a cytoplastic pattern. The histopathologic result of the lung nodule revealed multiloci necrosis of lung tissue accompanied with large amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Even though this could rarely be the presentation symptom (20), it generally appears more frequently with the progression of WG (16,18). Moreover, while pituitary participation may evolve with partial recovery and an adequate clinical response to systemic therapy (21), in most of the cases it has not been reported to improve without specific endocrine replacement therapy (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though this could rarely be the presentation symptom (20), it generally appears more frequently with the progression of WG (16,18). Moreover, while pituitary participation may evolve with partial recovery and an adequate clinical response to systemic therapy (21), in most of the cases it has not been reported to improve without specific endocrine replacement therapy (6).…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the clinical behavior of pituitary involvement in WG, as it was previously referred, it is mainly represented by any degree of CDI, combined with anterior hypopituitarism (17)(18)(19). Even though this could rarely be the presentation symptom (20), it generally appears more frequently with the progression of WG (16,18).…”
Section: Discussionmentioning
confidence: 99%
“…According to the prior study, less than 1% of patients with GPA have pituitary involvements [10]. Central DI is the most common presentation in patients who have pituitary involvement, frequently with combined anterior hypopituitarism, which usually develops after pulmonary or kidney involvement [4,11]. Meanwhile, Düzgün et al [5] reported a case of a patient with GPA who presented with central DI early in the disease course before renal and pulmonary involvement.…”
Section: Discussionmentioning
confidence: 99%
“…The present case is unique in that the patient initially presented with RPGN. On the other hand, from the perspective of GPA, the incidence of central nervous system involvement with GPA has been reported in about 20% of cases, with HCP representing less than 1% of these 9,35) . We could not obtain a complete view of relationships between GPA and HCP, PR3 ANCA and HCP, because cases including full details of the clinical course were scarce.…”
Section: Discussionmentioning
confidence: 99%